MENGKAJI VARIABEL ORGANIZATIONAL CITISENZHIP BEHAVIOR SEBAGAI MEDIASI DALAM HUBUNGAN VARIABEL KUALITAS KEHIDUPAN KERJA DAN KECERDASAN EMOSI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN DAMPAKNYA TERHADAP KINERJA ( Studi Pegawai Bank Muamalat Indone - Suparjati, Suparjati; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2018)
A this research was intended to analyze effect of Quality of work life , Emotional Intelligence to Employee Performanace and Organizational Citizemship Behavior as an mediation ( Studies in employees of Bank Muamalat Indonesia Semarang Branch ) Random sampling methode is used to 101 people.. For the analysis of this data using Sobel Test . T-test , F- test and determine coefficient we re used to test our hypotheses. The results of this research show that each dependent variable ; quality of work life is not significant effect on performance , can be interpreted organizational citizhensip behavior full mediation between quality of work life and performance. Emotional Intellegence is significant positive effect on performance. organizational citizenship behavior is significant positive effect on performance . Results of Sobel test is organiza tional citizenship behavior can be influence mediation for emotional ingtellegence and performance. Keywords : Quality of work life , emotional intellegence ,organizational citizhensip behavior , employee performance.